2002
DOI: 10.1038/415088a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a host protein essential for assembly of immature HIV-1 capsids

Abstract: To form an immature HIV-1 capsid, 1,500 HIV-1 Gag (p55) polypeptides must assemble properly along the host cell plasma membrane. Insect cells and many higher eukaryotic cell types support efficient capsid assembly, but yeast and murine cells do not, indicating that host machinery is required for immature HIV-1 capsid formation. Additionally, in a cell-free system that reconstitutes HIV-1 capsid formation, post-translational assembly events require ATP and a subcellular fraction, suggesting a requirement for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
266
1
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(297 citation statements)
references
References 28 publications
21
266
1
9
Order By: Relevance
“…As a negative regulator of the 2-5A/RNase L system, it acts in regulation of RNA stability of cell, might be also involved in a broad range of biological functions including viral infection, tumor cell proliferation, and antiapoptosis (3,4). The protein was then demonstrated as a host factor essential for assembly of primate lentivirus capsids, especially for HIV-1 (5,6). Recent evidence indicated new important roles of ABCE1 protein in translation initiation, elongation, termination, and ribosome recycling in eukaryotes (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…As a negative regulator of the 2-5A/RNase L system, it acts in regulation of RNA stability of cell, might be also involved in a broad range of biological functions including viral infection, tumor cell proliferation, and antiapoptosis (3,4). The protein was then demonstrated as a host factor essential for assembly of primate lentivirus capsids, especially for HIV-1 (5,6). Recent evidence indicated new important roles of ABCE1 protein in translation initiation, elongation, termination, and ribosome recycling in eukaryotes (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of capsid assembly in cell free systems indicated an energy-dependent step and an important role of ABCE1. ABCE1 is found in assembly intermediates at the plasma membrane but not in mature capsids (Zimmerman et al , 2002 ;Lingappa et al , 2006 ). Hereby, the nucleocapsid (NC) domain of Gag binds viral genomic RNA and is also required for interaction with ABCE1, albeit indirectly (Klein et al , 2011 ).…”
Section: Innate Immune and Virus Associated Functions Of Abce1 Revisitedmentioning
confidence: 99%
“…RNase-L is an interferon-dependent polysome-associated antiviral defense enzyme that is activated by 2 ′ -5 ′ oligoadenylates and degrades mRNA and single-stranded viral RNA in virus infected cells (Silverman , 2007 ), but also has a variety of additional functions (Chakrabarti et al , 2011 ). In 2002, ABCE1 was found to be required for the assembly of immature HIV-1 capsids and it has been suggested that it accounts for the ATP dependence of the rather poorly understood capsid assembly process (Zimmerman et al , 2002 ). While these early results made ABCE1 an interesting target for biomedical research and therapeutic intervention, the cellular function of ABCE1 remained unclear.…”
Section: Abc Enzymes: Versatile Molecular Machines or Switchesmentioning
confidence: 99%
See 2 more Smart Citations